Plasma neurofilament light levels associate with muscle mass and strength in middle‐aged and older adults: findings from GenoFit. Issue 3 (13th April 2022) - Pratt, Jedd; De Vito, Giuseppe; Segurado, Ricardo; Pessanha, Ludmilla; Dolan, Jackie; Narici, Marco; Boreham, Colin
Abstract: Background: Efforts to enhance diagnostic measures for sarcopenia have led to an increased focus on the screening utility of blood‐based biomarkers. In this regard, circulating neurofilament light chain (NfL) levels are a potent indicator of axonal damage and have been linked with several neurological disorders. However, despite the strong neurogenic contribution to skeletal muscle health, no studies have explored the relevance of NfL concentrations to sarcopenia. With that in mind, this study aimed to examine the association between plasma NfL concentration and sarcopenic domains. Methods: Three hundred adults aged between 50 and 83 years participated to this study (male participants, n  = 150; mean age: 64.2 ± 8.7 years and female participants, n  = 150; mean age: 63.9 ± 8.3 years). Body composition was assessed using dual‐energy X‐ray absorptiometry, and a skeletal muscle index (SMI) was calculated. Muscle strength was assessed with hand dynamometry. Sarcopenia was classified using the European Working Group on Sarcopenia in Older People criteria. Plasma NfL concentration was determined using a highly sensitive, enzyme‐linked immunosorbent assay. Results: Neurofilament light chain levels were associated with grip strength and SMI ( P  = 0.005 and P  = 0.045, respectively) and were significantly elevated in sarcopenic individuals, compared with non‐sarcopenic participants ( P  < 0.001). Individuals with pre‐sarcopenia (either low grip strength or low SMI) had significantly higher NfL levels, compared with healthy controls ( P  = 0.001 and P  = 0.006, respectively). Male participants with either low grip strength or low SMI had significantly raised NfL levels ( P  = 0.006 and P  = 0.002, respectively), while in female participants, NfL concentrations were significantly elevated only in those with low grip strength ( P  = 0.049). NfL concentration displayed acceptable diagnostic accuracy for sarcopenia (area under the curve = 0.726, P  < 0.001). Conclusions: Our study clearly demonstrates the indicative pertinence of circulating NfL levels to sarcopenic domains, supporting its potential use as a biomarker of sarcopenia. More studies are needed, however, to further illuminate the diagnostic value of circulating NfL. Future research should explore whether NfL levels are more powerfully linked with muscle strength than mass and whether sex mediates the relevance of NfL concentrations to sarcopenic phenotypes.